RITUAL KHANDURI BLANG: AGAMA DAN ADAT - Mugni, Abdul (JURNAL AL-IJTIMAIYYAH, 2018)
This article aims to see the phenomenon that occurs in rural communities amid the onslaught of electronic media in changing the way of thinking from traditional to rational, but people are not affected by a variety of media attacks, instead khanduri blang ritual activities themselves are exposed on social media such as Facebook. Sosiety communities perform rituals from generation to generation whose beliefs are based on the creator through symbolic activities whose meaning is understood and stored in deep chambers of thought, inherent as long as the union of spirits with bodies. Actualization of religious values is born through rituals.Keywords: Ritual, Religion, Culture